The reality of e-learning in the Institute of Science and Techniques of Physical and Sports Activities at the University of M’sila from the point of view of faculty members. - saadi, Idris; bachiri, benattia (sports creativity, 2023)
This study aims to identify the reality of e-learning in the Institute of Science and Techniques of Physical and Sports Activities at the University of M'sila from the point of view of faculty members. By identifying the possibilities, means and tools of e-learning and the extent to which teaching staff and students use e-learning, and The researchers used the descriptive approach and the questionnaire was used as a study tool The study sample consisted of 23 faculty members selected in a simple random manner of 23% The results of the study concluded, The reality of e-learning in the Institute of Science and Techniques of Physical and Sports Activities at the University of M'sila is acceptable at an intermediate level, Faculty and students use e-learning at a medium level as well as e-learning tools and available at a medium level. Keywords: e-learning, faculty members, university student, Institute of Science and Techniques of Physical and Sports Activities.